Coresidential Father Transitions and Biological Parents' Coparenting Quality in Early and Middle Childhood. (April 2017) - Martin, Anne; Ryan, Rebecca M.; Riina, Elizabeth M.; Brooks-Gunn, Jeanne
This study examined how the entrances and exits of biological and social fathers into and out of children's households were associated with biological parents' coparenting quality. Piecewise growth curve models tested for variation in these associations between child ages 1 and 3, 3 and 5, and 5 and 9. Data came from the Fragile Families and Child Wellbeing Study ( n = 2, 394). Results indicated that in all three age intervals, a biological father's entrance was associated with a contemporaneous increase in coparenting quality, whereas his exit was associated with a contemporaneous decrease. A biological father's exit between child ages 1 and 3, or 3 and 5, was associated with declining coparenting quality in subsequent intervals. A social father's entrance was consistently associated with a contemporaneous decrease in the biological parents' coparenting quality, whereas his exit was associated with a contemporaneous increase between ages 3 and 5, and 5 and 9.